Incidence of Chiari-like Malformation/Syringomyelia in a Cohort of Small Dog Breeds Scanned Using MRI over a Period of 8 Years in the Netherlands - Fredrik Hoholm; Karin Bruining-Staal; Paul J.J. Mandigers (Pets, 2024)
Background: Chiari-like malformation (CM), Syringomyelia (SM) and middle ear effusion (MEE) are frequently observed disorders in Cavalier King Charles Spaniels (CKCSs), Pomeranians, and less frequently the Griffon. There are a few reports in which small dogs have been identified as suffering from CM/SM. Methods: From all MRI centers based in the Netherlands, MRI scans for small dog breeds performed for various reasons over a period of 8 years were collected. Scans that enabled a CM and/or SM evaluation were included and evaluated. Results: In total, 177 MRI scans were included. CM could be evaluated in 163 out of 177 dogs. In 63 dogs, no CM was observed, while 100 dogs had CM. SM could be evaluated in 144 out of 177 dogs. No SM was seen in 56 dogs and SM was seen in 88 dogs. Both CM and SM were seen in high frequency in the Chihuahua, French Bulldog, Griffon, and Pug but did also occur in lower frequencies in various other small breed dogs and crosses. CM and/or SM does occur in various other small dog breeds and crosses suggesting that it is indeed a type-related disorders. As it can cause serious clinical signs breeders should be aware of the risk of CM/SM when breeding with these small dog breeds.